A novel sensor for organic solvent vapors based on conductive amorphous polymer composites: carbon black/poly(butyl methacrylate) - Dong, X.M.; Fu, R.W.; Zhang, M.Q.; Zhang, B.; Li, J.R.; Rong, M.Z.
Conductive composites from carbon black/poly(butyl methacrylate)(CBPBMA)are synthesized through polymerization filling. The experimental results indicate that relatively low percolation threshold (~6wt